Suomalaiset yritykset kansainvälisten veroreformien pyörteissä - Olli Ropponen; Marika Viertola; Seppo Kari; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2023)
– International corporate tax system does not succeed very well in taxing the cross-border business of the multinational enterprises. Therefore, both the European Union (EU) and the Organization for Economic Cooperation and Development (OECD) have proposed several tax reforms. We recognize in this Etla Report the most central corporate tax reform proposals and evaluate their effects on the tax burden of the Finnish companies and on the tax revenues in Finland. The common consolidated corporate tax base (CCCTB) proposed by the OECD, would reduce the investment incentives by increasing the tax burden of companies. It would also reduce the corporate tax revenues in Finland. The reallocation of residual profits (Pillar 1) would neither affect Finnish companies nor tax revenues in Finland. Minimum tax (Pillar 2) is the only reform that provides favorable outcomes for both companies and government. It increases the investment incentives of companies by reducing their tax burden, while at the same time increasing the tax revenues in Finland. The proposed 15 percent minimum tax rate is better option from both the company and the government perspective than higher minimum tax rates.
Keywords: H25; H71; F21; F23; G11; 330; International corporate taxation; Multinational enterprises (MNEs); Investments; Business in Europe: Framework for Income Taxation (BEFIT); Pillar 1; Pillar 2; Common (Consolidated) Corporate Tax Base (C(C)CTB)